Influence of irrigation scheduling on grain yield, water use and soil moisture status in direct seeded basmati rice - CHOUDHARY, KARTIKEYA; BHARTI, VIJAY; SAHA, ANURADHA; DEVEDEE, ANOOP KUMAR (Journal of Soil and Water Conservation, 2021)
A field experiment was conducted during kharif, 2015 at Jammu to study the effect of irrigation scheduling on grain yield, water use and soil moisture status in direct seeded basmati rice. The experimental results revealed that among the five irrigation schedules, control though at par with irrigation at 2 days interval through sprinkler at 150% PE recorded significantly higher grain yield. Varieties also responded significantly in terms of grain yield. Water use expressed as net water expense and volume of water use was found to be maximum in control with minimal water productivity whereas minimum net water expense and volume of water use was recorded in sprinkler irrigation at 125% PE. Water productivity was observed highest in irrigation at 2 days interval through sprinkler at 150% PE with 36 per cent saving of water. The soil moisture status monitored at periodic intervals before and after irrigation showed 36.40% increase in moisture content at 0-20 cm depth and 9.86% increase in moisture content at 20-40 cm depth over the initial values.